Association of XRCC1, XRCC3, and XPD genetic polymorphism with an increased risk of hepatocellular carcinoma because of the hepatitis B and C virus - Gulnaz, Asma; Sayyed, Ali H; Amin, Farah; Khan, Abrar ul Haq; Aslam, Muhammad A; Shaikh, Rehan S; Ali, Muhammad (European journal of gastroenterology & hepatology, 2013)
The south-east Asian and sub-Saharan African populations are the most susceptible to hepatocellular carcinoma (HCC). We aimed to establish whether XRCC1, XRCC3, and XPD are associated with liver cancer in Pakistan and to examine the interaction of hepatitis B virus (HBV) or hepatitis C virus (HCV) with repaired genes in the occurrence of liver cancer. We enrolled 74 healthy individuals, 75 had either HBV or HCV, and 50 were HCC patients. The characteristic information of all the study participants were collected through a standard interviewer-administered questionnaire. The PCR-RFLP was used to identify the genotype of the patients. The results of our study indicated that the patients infected with HBV or HCV had a four or three-fold greater risk of developing liver cancer. Patients older than 55 years of age had a significantly higher risk of developing cancer compared with younger patients. The homozygous wild types Arg/Arg for 280 and Thr/Thr for 241 were more frequent in the controls than in the cases. The allelic frequency of mutant 280His and 399Gln was more pronounced among HCC cases than the controls or the HBV-infected patients. The frequency of the XPD gene in the controls was in Hardy-Weinberg equilibrium, indicating that the gene played a protective role in the Pakistani population. XRCC1 or XRCC3 was associated with liver cancer in the Pakistani population; however, the XPD gene played a vital role in the repair of DNA damage.